The AI Liability Frontier: Can Doctors Be Sued for Relying on Artificial Intelligence? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The AI Liability Frontier: Can Doctors Be Sued for Relying on Artificial Intelligence? The integration of Artificial Intelligence (AI) into clinical pra...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning